Physical principles of hyperspectral sensing - Ualiyeva Р.М.; Tukhfatullin, T.A.; Boytsova Е.Л.; Kaverina М.М. (Recent Contributions to Physics, 2024)
Hyperspectral technologies combine spectrophotometric methods and imaging techniques, enabling the study of the spectral composition of radiation emitted by an object. These technologies are widely used in various fields of science and technology. In recent years, hyperspectral imaging has been particularly active in agronomy for diagnosing plant diseases and detecting biological anomalies. This work is devoted to a comparative analysis of the main types of hyperspectral cameras: dispersive, interferometric, and filter-based. Their characteristics and the physical principles underlying hyperspectral imaging are analysed. The choice of the optimal type of hyperspectral camera depends on specific application requirements. Dispersive cameras are characterized by high acquisition speed and broad spectral coverage but require bulky optical components and significant costs. Interferometric systems offer high spectral sensitivity, but their application is limited by dependence on lighting stability. Filter-based cameras provide flexibility in configuration and potential compactness but may have mechanical and spectral limitations due to filter characteristics. The overview of the main types of hyperspectral cameras, their key characteristics, and fields of practical application is presented.